Delinquency in a Birth Cohort II: Philadelphia, 1958-1988 - Figlio, Robert M. ([Verlag nicht ermittelbar], 1990)
The purpose of this data collection was to follow a birth cohort born in Philadelphia during 1958 with a special focus on delinquent activities as children and as adults. The respondents were first interviewed in DELINQUENCY IN A BIRTH COHORT IN PHILADELPHIA, PENNSYLVANIA, 1945-1963 (ICPSR 7729). Part 1 offers basic demographic information, such as sex, race, date of birth, church membership, age, and socioeconomic status, on each cohort member. Two files supply offense data: Part 2 pertains to offenses committed while a juvenile and Part 3 details offenses as an adult. Offense-related variables include most serious offense, police disposition, location of crime, reason for police response, complainant's sex, age, and race, type of victimization, date of offense, number of victims, average age of victims, number of victims killed or hospitalized, property loss, weapon involvement, and final court disposition. Part 4, containing follow-up survey interview data collected in 1988, was designed to investigate differences in the experiences and attitudes of individuals with varying degrees of involvement with the juvenile justice system. Variables include individual histories of delinquency, health, household composition, marriage, parent and respondent employment and education, parental contacts with the legal system, and other social and demographic variables.